2018
DOI: 10.4081/or.2018.7531
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcome of the different HemiCAP and UniCAP knee implants: A systematic and comprehensive review

Abstract: The focal metallic cartilage resurfacing is a surgical method that offers an appropriate step between the biological techniques and arthroplasty in middle-aged patients with full-thickness cartilage defects. The advantages of this technique are that it addresses the defect, respects healthy tissues and provides stability and contoured surface similar to a full arthroplasty. A systematic review was conducted according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Dhollander et al described a statistically significant increase in degenerated changes according to the Kellgren and Lawrence classification in the treated knees, based on nine out of 18 patients that were radiographically evaluated at 24 months [6]. It seems to be clear that progression to OA is not completely avoided with this technique [23], and further studies are therefore needed to better define the role of focal metallic implants in preventing the progression to OA. Becher et al described the 12-year follow-up of two cases that have been managed by means of a prosthetic resurfacing for full-thickness cartilage defect, and comparing the first post-operative to 12-year follow-up X-rays, the radiographic results demonstrated no signs of periprosthetic loosening, preservation of joint space and no change in the osteoarthritic stage [24].…”
Section: Discussionmentioning
confidence: 99%
“…Dhollander et al described a statistically significant increase in degenerated changes according to the Kellgren and Lawrence classification in the treated knees, based on nine out of 18 patients that were radiographically evaluated at 24 months [6]. It seems to be clear that progression to OA is not completely avoided with this technique [23], and further studies are therefore needed to better define the role of focal metallic implants in preventing the progression to OA. Becher et al described the 12-year follow-up of two cases that have been managed by means of a prosthetic resurfacing for full-thickness cartilage defect, and comparing the first post-operative to 12-year follow-up X-rays, the radiographic results demonstrated no signs of periprosthetic loosening, preservation of joint space and no change in the osteoarthritic stage [24].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recently, a systematic review of the literature evaluated the outcomes of focal metallic inlay resurfacing for the treatment of isolated cartilage defects of the femoral condyles concluding that this system seems to be a viable option for carefully selected patients. The review reported a significant improvement in knee function and pain, also if many doubts remain as regards progression of osteoarthritis (6).…”
mentioning
confidence: 90%
“…In this scenario has gained popularity the use of focal metallic implant, both for primary or revision surgery (6). The focal metallic cartilage resurfacing is a surgical method that offers an appropriate step between regenerative procedures and replacement surgery, especially in middleaged patients with full-thickness chondral lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important to position implants accurately to avoid step offs or increased pressure on the opposite cartilage surface [ 18 , 86 ]. In addition, Malahias et al [ 87 ] reported that Arthrosurface inlay implants were associated with a postoperative effusion. They stated that these procedures should only be used if prior biological treatments failed.…”
Section: Focal Chondral Defects and Focal Resurfacingmentioning
confidence: 99%